2021
DOI: 10.33448/rsd-v10i5.14984
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à disfunção temporomandibular em estudantes de fisioterapia: estudo transversal

Abstract: O objetivo deste estudo é avaliar a prevalência e fatores associados à DTM em estudantes concludentes do curso de Fisioterapia. Trata-se de um estudo transversal, realizado com estudantes do oitavo ao décimo período, por meio da aplicação de questionários, visando identificar o perfil sociodemográfico e acadêmico, hábitos parafuncionais, severidade da DTM e o nível de ansiedade. Os dados foram analisados no programa Statistical Package for the Social Sciences Aplicou-se o Teste de Tendência Linear e considerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Correlating the etiology of temporomandibular disorder and its incidence, high levels of stress and anxiety are its biggest cause during graduation, as this promotes high levels of muscular tension in students, fluctuations in the emotional state, and the progression of musculoskeletal disorders. Thus, a range of studies have revealed the relationship between depression and anxiety with the development of temporomandibular joint dysfunction [24].…”
Section: Resultsmentioning
confidence: 99%
“…Correlating the etiology of temporomandibular disorder and its incidence, high levels of stress and anxiety are its biggest cause during graduation, as this promotes high levels of muscular tension in students, fluctuations in the emotional state, and the progression of musculoskeletal disorders. Thus, a range of studies have revealed the relationship between depression and anxiety with the development of temporomandibular joint dysfunction [24].…”
Section: Resultsmentioning
confidence: 99%